2004
DOI: 10.30544/379
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Newtonian and Fourier thermal analysis techniques for calculation of latent heat and solid fraction of aluminum alloys

Abstract: The cooling curve analysis (CCA) has been used extensively in the metal casting industry, usually to predict alloy composition and microstructure constituents. The use of CCA can be expanded to other areas of solidification if the zero curves can be properly calculated. In this paper the Newtonian and Fourier techniques of zero curve determination are described. These techniques were developed to calculate latent heat and to determine the correlations between solid fraction and temperature/time for Al-7 wt%Si … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 4 publications
0
35
0
Order By: Relevance
“…Emadi et.al. reported that they used a crucible whose thermal mass was less than 0.5% of the total thermal mass of the system [7]. Yet, the thermal capacity of resin-coated sand molds used in this study were measured 117 J/K, while that of pure tin is 83 J/K.…”
Section: Evaluation Of Ntamentioning
confidence: 92%
“…Emadi et.al. reported that they used a crucible whose thermal mass was less than 0.5% of the total thermal mass of the system [7]. Yet, the thermal capacity of resin-coated sand molds used in this study were measured 117 J/K, while that of pure tin is 83 J/K.…”
Section: Evaluation Of Ntamentioning
confidence: 92%
“…It is based on the measurement and analysis of the temperature of cooling sample in a small cup. CA-CCA techniques include the determination of liquidus and solidus temperature [5], grain refinement [6,7], phase transitions [4,8,9], dendrite coherency point [2,10], solid fraction, and latent heat [4,11,12]. Cooling curve analysis has been applied using various methods for several types of alloys in metallurgical applications [2][3][4][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years computer-aided cooling curve analysis (CA-CCA) has been used to determine thermo-physical properties of alloys, latent heat and solid fraction. Being very simple to setup it can be widely used, especially in industries [7][8][9][10][11]. The foremost use of cooling curves has been the determination of arrest points during solidification.…”
Section: Introductionmentioning
confidence: 99%